Legal Protection of Banks That Give Business Capital Credit Without Collateral - Mahila, Syarifa; Hariss, Abdul; Maryati, Maryati; Fauzia, Nur (Jurnal Bina Mulia Hukum, 2024)
This research aims to analyze legal considerations for business credit without collateral and analyze legal protection for banks that provide business credit without collateral. The research method used in this research is normative juridical. The results of the research show that business credit providers have legal protection if business credit without collateral is carried out through preventive protection, which of course requires a formula based on the contents of credit agreement that has been determined and must be implemented if a default occurs. There is a need for the contents of agreement to be precise so it can be binding and stated in the credit agreement, which of course has also been agreed upon by all parties; legal protection, which is considered repressive; as a reference in taking steps if there is a risk of loss from the business carried out by the capital provider; and the need for an institution to Alternative Dispute Resolution in the Financial Services Sector (LAPS Financial Services Sector) is an institution that resolves disputes in the financial services sector outside of court. If the credit repayment stage is problematic, it is necessary to resolve it without harming both parties based on the amount of credit given is not a large amount. So, an Alternative Financial Services Sector Dispute Resolution Institution (Financial Services Sector LAPS) is needed to resolve disputes through face-to-face meetings before a mediator or arbitrator, electronic media, or document inspection.